Empowering Village Communities through Character Education: The Impact of Student Engagement Programs in Patakbanteng Village - Saifulloh, Faza; Jumini, Sri; Mahmud, insan; Suwondo, Adi; Mukromin, M; Firdaus, F (AL-ISHLAH: Jurnal Pendidikan, 2026)
Character education in village communities is essential for strengthening social responsibility, cooperation, independence, and moral awareness. However, evidence on how student engagement programs contribute to community-based character formation remains limited. This study examined a student engagement program implemented by the Student Executive Board of Universitas Sains Al-Qur’an in Patakbanteng Village, Wonosobo, Indonesia. A sequential exploratory mixed-method design was used. Qualitative data were collected through observation, interviews, and documentation to identify emerging character values during program activities. These findings informed a post-program questionnaire administered to community participants. Data were analyzed thematically and descriptively using percentage-based categorization. The findings showed that the program was associated with positive character outcomes among participating community members. The highest score was found in responsibility at 91.67%, followed by initiative and creativity at 90.67%, caring and independence at 90.33%, mutual cooperation at 90%, hard work and exemplary behavior at 89.67%, and discipline at 88%. All indicators were categorized as “very good.” Qualitative findings indicated that participatory activities, mentoring, group discussions, and collaborative problem-solving encouraged community members to become more active, disciplined, cooperative, and confident in managing local initiatives. The study suggests that student engagement programs can serve as contextual spaces for character education and community empowerment. Nevertheless, because the quantitative data were collected only after the program, the findings should be interpreted as post-program perceptions and observed tendencies rather than causal evidence of program impact. Future studies should use pre-post measurements, validated instruments, and comparison groups.